Considering Quality of Life while Repudiating Disability Injustice: A Pathways Approach to Setting Priorities. Issue 2 (June 2019) - Persad, Govind
This article proposes a novel strategy, one that draws on insights from antidiscrimination law, for addressing a persistent challenge in medical ethics and the philosophy of disability: whether health systems can consider quality of life without unjustly discriminating against individuals with disabilities. It argues that rather than uniformly considering or ignoring quality of life, health systems should take a more nuanced approach. Under the article's proposal, health systems should treat cases where (1) quality of life suffers because of disability-focused exclusion or injustice differently from cases where (2) lower quality of life results from laws of nature, resource scarcity, or appropriate tradeoffs. Decisionmakers should ignore quality-of-life losses that result from injustice or exclusion when ignoring them would improve the prospects of individuals with disabilities; in contrast, they should consider quality-of-life losses that are unavoidable or stem from resource scarcity or permissible tradeoffs. On this proposal, while health systems should not amplify existing injustice against individuals with disabilities, they are not required to altogether ignore the potential effects of disability on quality of life.